Cosmic - Cottrell Boyce, Frank (Walden Pond Press, 2011)
Twelve-year-old Liam, who looks like he is thirty and is tired of being treated like he is older than he actually is, decides he is going to pose as the adult chaperone on the first spaceship to take civilians into space, but when he ends up in outer space with a group of kids and no adult supervision, he must think fast to make things right.